Investigating the Medicinal Potential of Lavatera cashmeriana Leaf Extract: Phytochemical Profiling and In Vitro Evaluation of Antimicrobial, Antioxidant, and Anticancer Activities - Mohmmad Ashaq Sofi; Mohd Abass Sofi; Anima Nanda; Kasi Thiruvengadam; B. K. Nayak (Hindawi Limited, 2024)
This study investigated the medicinal potential of Lavatera cashmeriana, a plant traditionally known for its therapeutic properties. The aim was to identify the phytocompounds in L. cashmeriana leaf extract and evaluate its antibacterial, antioxidant, and anticancer effects. Gas chromatography-mass spectrometry analysis was employed to characterize the phytochemical composition of the ethanol extract derived from L. cashmeriana leaves. The antimicrobial potential was assessed through the well diffusion technique, targeting Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans. The 2,2-diphenyl-1-picrylhydrazyl assay was conducted to assess antioxidant capabilities, while cytotoxicity against the A549 cancer cell line was determined via the MTT assay. GC-MS analysis identified ten different compounds, with phytol, 1-Eicosanol, and 2,6,10-trimethyl,14-ethylene-14-pentadecne being the most prevalent. The extract exhibited notable antimicrobial efficacy against all bacteria with MIC values ranging from 62.5 to 250 µg/mL. However, C. albicans did not respond. The extract exhibited antioxidative properties with an IC50 value of 86 µg/mL and cytotoxicity with an IC50 value of 69.95 µg/mL against the A549 cancer cell line. The results derived from this study supported the historical use of L. cashmeriana as a medicinal plant and suggested that it can potentially treat a wide range of medical ailments. The identified phytocompounds and the demonstrated antibacterial, antioxidant, and anticancer effects provide scientific evidence for its medicinal properties. However, further investigations are needed to fully understand its safety profile, efficacy, and mechanism of action before recommending it for therapeutic purposes.